Apakah Tingkat Pendidikan dan Frekuensi Senam Aerobik berhubungan dengan Status Gizi? - Bella Cloudia Chairudin; Aaltje Ellen Manampiring; Jeini Ester Nelwan (Universitas Sam Ratulangi, 2021)
Background: Nutritional status is also a person's physical condition which is determined by one or a combination of nutritional measures such as body mass index. Nutritional status is indirectly influenced by the frequency of aerobic/ anaerobic exercise and the level of education. The purpose of this study was to analyze the correlation between education level and frequency of aerobic exercise with nutritional status of members of the Sports Health Center of Health Office North Sulawesi Province. Methode: This is a correlational research with a cross-sectional approach. This research was conducted in June-July 2020 at the Community Sports Health Center of Health Office North Sulawesi Province. This study used 30 respondents. The variables of this study were nutritional status, level of education and frequency of aerobic exercise. This study uses secondary data from existing member at the Community Sports Health Center. Data were tested using Fisher's Exact test. Result: The results showed that 27 respondents had a BMI <18.5-22.9, 24 respondents had S1/ D3 degree and 15 respondents were aerobic exercise frequency as much as 37-50 times. The results of this study indicated that there was no correlation between education level with nutritional status (p = 0.501) and there was no correlation between the frequency of aerobic exercise with nutritional status (p = 1,000). Conclusion: The conclusion of this study is that the level of education and the frequency of aerobic exercise are not correlation with the nutritional status of the members of the Sports Health Center.